THE THE CHALLENGE OF PRO-POOR CULINARY TOURISM DEVELOPMENT: AN ANALYSIS OF THE INDONESIAN GOVERNMENT'S PROMOTION WEBSITE - Purnomo, Agustina (Politeknik Pariwisata NHI Bandung, 2023)
This study aims to elaborate on tourism promotion on the government's official website to explain the challenge of pro-poor culinary tourism development in Indonesia. The qualitative content analysis was used to analyze 224 articles on the government's official tourism promotion website. The researcher processed by counting the presence of the information. The data processing was counting the presence of the information. The researchers read all the text and put code 1 for the information appearance and 0 for the absence. The number of information presentations indicated the government's focus. The government was not put pro-poor culinary tourism development as their focus. The provision of optimal benefits for the poor was not reflected in the promotion of culinary tourism on the government's official website. The challenge for the pro-poor culinary tourism development of the Indonesian government is to translate the goals of tourism development into adequate tourism promotion. The research limitation was that the researcher did not confirm the data through interviews with the website managers. Further research is recommended to conduct interviews with website managers to explain the reasons for choosing information on the website. There was limited research on the government's official culinary tourism promotion website. This study contributed to comprehending what the government should do to promote culinary in the poor alleviation context.